Physical properties and sensory acceptance of red palm olein-based low-fat ice cream added with guar gum and xanthan gum as stabilizers - Ismail, A.H.; Wongsakul, S.; Ismail-Fitry, M.R; Rozzamri, A.; Mat Yusoff, M. (Rynnye Lyan Resources, 2020)
Red palm olein (RPOL) is rich in nutritional and antioxidant compounds including carotenoids, tocopherols, and tocotrienols which makes it beneficial in food applications. However, to maintain the colloidal stability of RPOL in ice cream is challenging. Therefore, this study was carried out to formulate value-added ice creams supplemented with RPOL (0.1-5.0% w/w) in combination with guar gum (GG; 0.0-0.4% w/w) or xanthan gum (XG; 0.0-0.4% w/w) as stabilizers. Physical properties and sensory acceptance of these ice creams were determined in comparison with selected commercial ice cream samples (CM-ice creams). Ice cream with 0.1% RPOL and 0.4% guar gum resembled CM-ice creams in terms of viscosity (9.08±0.05 Pa.s.), hardness (3.59±3.12 kg), and amount of melted ice cream/30 min (62.00±2.83%). Meanwhile, ice cream with 0.1% RPOL and 0.4% xanthan gum was similar with CM-ice creams in their viscosity (9.19±0.04 Pa.s.) and hardness (0.60±0.25 kg), yet was relatively lower in the amount of melted ice cream/30 min (33.46±5.06%). All ice creams appeared red and yellow due to the presence of RPOL, and the colour intensity was enhanced with the presence of the stabilizers. The RPOL-based ice creams displayed lower score in sensory properties than those of CM-ice creams, thus highlighted the necessary attributes that need to be improved in future studies.